Analysis of Students' Misconception on General Biology Concepts Using Four-Tier Diagnostic Test (FTDT) - Trio Ageng Prayitno; Nuril Hidayati (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
This research aims to determine the percentage of students' misconception on general biology concepts using the Four-Tier Diagnostic Test (FTDT). This research method is descriptive research. The research sample was 100 students from IKIP Budi Utomo, Universitas Nusantara PGRI Kediri, and Universitas PGRI Madiun. The research instrument is the FTDT question. The data collection techniques by distributing FTDT questions via Google Form to students using WhatsApp. The data analysis technique was done by quantitative descriptive. The results showed that 25% of students understood the concept, 39% of students had misconception, 23% of students guessed the answer, and 13% of students lack knowledge. The lowest student misconception on the concept of structure and function at all levels of biological organization is 20% and the highest misconception on the concept of the definition of biology is 65%. While the sequence of the third category of students' highest misconception is 65% misconception, 11% false positive, and 12% false negative. The results of this study are important to provide advice to lecturers when teaching general biology to always provide correct information, valid reading sources, valid learning media, and appropriate learning models so that there are no misconceptions among students.